Characterisation of laser produced plasmas - Doggett, Brendan (Trinity College (Dublin, Ireland). School of Physics, 2006)
This thesis describes the apphcation of planar Langmuir probes in laser produced plasmas. The influence of the ion flow on the probe behaviour and its effect on the measured plasma parameters has been investigated for different probe orientations. The expansion dynamics of the laser produced plasma were studied using the probes and the results obtained were compared to adiabatic expansion models.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin